Calamities causing loss of museum collections: a historical and global perspective on museum disasters - Tyler, Michael J.; Fucsko, Lydia A.; Roberts, J. Dale (Zootaxa, 2023)
With alarming frequency, significant collections in natural history museums have been destroyed or damaged through insurrections, cyclones, wars, fires, floods, or earthquakes particularly in the nineteenth century but continuing into the twentieth century with World War II bombings, fires, and earthquakes being the primary causes of loss in fifty-seven institutions across thirty countries. We review the loss or damage of museum collections globally, and their varied causes. We emphasize the benefits of dispersal of a sample of paratypes across institutions as an essential feature of taxonomic practice. We argue that museums do not own type material but are acting as perpetual custodians of type material on behalf of science and society in general, and that museums, therefore, have an obligation to minimize the risk to their collections. The significance of the loss of type material would be ameliorated if, when there are numerous paratypes or syntypes, members of a type series were distributed among several institutions. This is currently common practice but historically this was not always the case and might not be possible if only a single holotype is available. We also reaffirm the need for scientists around the globe to develop specific protocols to protect collections of biological and cultural materials from loss or damage from natural and human-created disasters now and into the future. We comment on recent moves to modify the Zoological Code of Nomenclature to allow the use of images as “type” material when describing new species with the image serving as a substitute for “physical” specimens deposited in museum collections. Although our focus is on herpetological collections, our particular interest and area of expertise, our observations apply broadly to all collections, including those of animals, plants, and anthropological or ethnographic material.